Fresh biochar application provokes a reduction of nitrate which is unexplained by conventional mechanisms - Llovet, Alba (2021)
Soil-applied biochar has been reported to possess the potential to mitigate nitrate leaching and thus, exert beneficial effects beyond carbon sequestration. The main objective of the present study is to confirm if a pine gasification biochar that has proven able to decrease soil-soluble nitrate in previous research can indeed exert such an effect and to determine by which mechanism. For this purpose, lysimeters containing soil-biochar mixtures at 0, 12 and 50 t biochar ha−1 were investigated in two different scenarios: a fresh biochar scenario consisting of fresh biochar and a fallow-managed soil, and an aged biochar scenario with a 6-yr naturally aged biochar in a crop-managed soil. Soil columns were assessed under a mimicked Mediterranean ambient within a greenhouse setting during an 8-mo period which included a barley crop cycle. A set of parameters related to nitrogen cycling, and particularly to mechanisms that could directly or indirectly explain nitrate content reduction (i.e., sorption, leaching, microbially-mediated processes, volatilisation, plant uptake, and ecotoxicological effects), were assessed. Specific measurements included soil solution and leachate ionic composition, microbial biomass and activity, greenhouse gas (GHG) emissions, N and O isotopic composition of nitrate, crop yield and quality, and ecotoxicological endpoints, among others. Nitrate content reduction in soil solution was verified for the fresh biochar scenario in both 12 and 50 t ha−1 treatments and was coupled to a significant reduction of chloride, sodium, calcium and magnesium. This effect was noticed only after eight months of biochar application thus suggesting a time-dependent process. All other mechanisms tested being discarded, the formation of an organo-mineral coating emerges as a plausible explanation for the ionic content decrease.